HUBUNGAN EFIKASI DIRI DENGAN PERENCANAAN KARIR SISWA KELAS XI SMAN 11 JAKARTA - Susanti, Deviana Ramadhani; Marsinun, Rahmiwati (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the relationship between self-efficacy and career planning for class XI students of SMAN 11 Jakarta. The research method used is a correlational quantitative research method. The population used in this study were students of class XI SMAN 11 Jakarta, totaling 210 students divided into 6 classes (class XI Science totaling 3 classes and class XI Social Sciences totaling 3 classes). The sampling technique in this study used a simple random sampling technique. The results showed that the hypothesis was accepted, meaning that there was a relationship between variable self efficacy (X) and variable career planning (Y). This was obtained at a significance value of 0.00 less than 0.05 (0.00 <0.05) meaning that the relationship between self-efficacy and career planning was obtained at (0.724) indicates a positive relationship direction. It can be concluded that if the self-efficacy variable is high, then the career planning variable is high. Conversely, if the self-efficacy variable is low then the career planning variable is low.